Comparing the Continuous Geboes Score With the Robarts Histopathology Index: Definitions of Histological Remission and Response and their Relation to Faecal Calprotectin Levels. (4th September 2019) - Magro, Fernando; Lopes, Joanne; Borralho, Paula; Lopes, Susana; Coelho, Rosa; Cotter, José; Dias de Castro, Francisca; Tavares de Sousa, Helena; Salgado, Marta; Andrade, Patrícia; Vieira, Ana Isabel; Figueiredo, Pedro; et al.
Abstract: Background and Aims: The histological status of ulcerative colitis [UC] patients in clinical and endoscopic remission has gained space as an important prognostic marker and a key component of disease monitoring. Our main aims were to compare two histological indexes—the continuous Geboes score [GS] and the Robarts Histopathology index [RHI]—regarding their definitions of histological remission and response, and the ability of faecal calprotectin [FC] levels to discriminate between these statuses. Methods: This was an analysis of three prospective cohorts including 422 patients previously enrolled in other studies. Results: The two continuous scores [GS and RHI] were shown to be significantly correlated [correlation coefficient of 0.806, p < 0.001] and particularly close regarding their definition of histological response: 95% and 88% of all patients classified as having/not having [respectively] histological response according to RHI also did so according to GS. Moreover, median FC levels in patients with histological response were lower than those in patients without histological response [GS: 73.00 vs 525.00, p < 0.001; RHI: 73.50 vs 510.00, p < 0.001]; a similar trend was observed when FC levels of patients in histological remission were compared to those of patients with histological activity [GS: 76.00 vs 228.00, p < 0.001; RHI: 73.50 vs 467.00, p < 0.001]. FC levels allowed us to exclude the absence of histological remission [according to RHI] and absence of histological response [according to RHI and GS], with negative predictive values varying from 82% to 96%. However, optimization of the FC cut-off to exclude the absence of histological remission, as for the continuous GS, falls within values that resemble those of the healthy population. Conclusion: The continuous GS and RHI histological scores are strongly correlated in their definitions of histological response. An absence of histological remission could only be excluded at physiological levels of FC.